Private Law Codifications in East Central Europe - Veress, Emőd (Lectures on East Central European Legal History, 2023)
The codification of civil law implies the creation of a fundamental law in a private context. The process itself is fascinating: the social and political context that shaped East Central Europe’s civil codes. What models were used in the codification process and who were the key players? English language legal history works generally speak very briefly of East Central Europe as a region of the model being followed and may dedicate a few lines to mentioning which civil code is a translation or adoption of which Western model. In fact, this story is much more complex. Adaptation included innovative elements, and the way in which the courts applied these codes revealed the region’s specificities. Most civil codes of East Central Europe cannot be considered transplants and are as original as the important codes in different world regions. This chapter firstly analyzes the two 19th-century waves of codification. Secondly, the chapter examines the other three waves of codification in the 20th century. The emphasis is on the specificities of East Central Europe and on the comparative legal method.KEYWORDS: codification, civil codes, East Central Europe, Croatia, Czechia, Hungary, Poland, Romania, Serbia, Slovakia, Slovenia.